2009
DOI: 10.1051/0004-6361/200911926
|View full text |Cite
|
Sign up to set email alerts
|

Rate and nature of false positives in the CoRoT exoplanet search

Abstract: Context. The CoRoT satellite searches for planets by applying the transit method, monitoring up to 12 000 stars in the galactic plane for 150 days in each observing run. This search is contaminated by a large fraction of false positives, caused by different eclipsing binary configurations that might be confused with a transiting planet. Aims. We evaluate the rates and nature of false positives in the CoRoT exoplanets search and compare our results with semiempirical predictions. Methods. We consider the detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 16 publications
1
47
1
Order By: Relevance
“…However, it is more difficult to find this secondary around faint targets because the signal-to-noise ratio is poorer, which possibly makes the contamination of binaries higher at the faint end, reducing the performance of the planet detection. Recently, Almenara et al (2009) have published a detailed study evaluating the rates and nature of false positives in the first CoRoT fields observed, which also provides insight into the nature of the planetary populations detected with CoRoT.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is more difficult to find this secondary around faint targets because the signal-to-noise ratio is poorer, which possibly makes the contamination of binaries higher at the faint end, reducing the performance of the planet detection. Recently, Almenara et al (2009) have published a detailed study evaluating the rates and nature of false positives in the first CoRoT fields observed, which also provides insight into the nature of the planetary populations detected with CoRoT.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most cases photometry alone does not allow the planetary nature of the detected transits to be established. Indeed, several stellar configurations can mimic planetary transits (e.g., Almenara et al 2009;Bouchy et al 2009a), including undiluted eclipsing binaries with low-mass stellar companions or diluted eclipsing binaries, namely blends. Whereas such impostors represent the majority of transiting planet candidates detected by ground-based surveys or even by CoRoT, it has been argued from statistical studies that they should be particularly rare for Kepler candidates (e.g., Morton & Johnson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…First general results on the types of false alarm sources are given in Almenara et al (2009) , Fig. 6.…”
Section: Results From the Photometric Follow-upmentioning
confidence: 99%